Fire Bombings and Forgotten Civilians: The Lawsuit Seeking Compensation for Victims of the Tokyo Air Raids 焼夷弾空襲と忘れられた被災市民―東京大空襲犠牲者による損害賠償請求訴訟 - Cary Karacas (Asia-Pacific Journal, 2011)
In 2007, an extraordinary apology by Japanese Prime Minister Abe Shinzō appeared in print. It begins with an acknowledgment that Japan's indiscriminate bombing of civilians living in the Nationalist Chinese wartime capital of Chongqing beginning in 1938 violated international law and gave the United States a justification for its own devastating incendiary raids on Japan's capital. The prime minister also admits that, by not capitulating to the United States once defeat became inevitable, the Japanese government essentially permitted the firebombing of Tokyo and thereafter the rest of urban Japan in 1945. To show the sincerity of its apologetic stance toward Tokyo air raid victims, the state agreed to provide financial compensation to survivors and bereaved family members, conduct a comprehensive survey of the dead, and build a memorial both to honor them and to serve as a reminder that the air raids had occurred. The letter exists only as a suggested template, however, written by plaintiffs who sued the Japanese government seeking such an apology and compensation of 1.23 billion yen (approximately $15 million). In March 2007, sixty-two years after the catastrophic Great Tokyo Air Raid forever changed their lives, 112 survivors and bereaved family members announced their intent to sue the government for redress. The following month, the plaintiffs, the oldest of whom was eighty-six and whose average age was seventy-four, filed the suit with the Tokyo District Court.